Hubungan Kekuatan Otot Quadriceps dan Posisi Patella terhadap Fungsi Lutut pada Olahragawan - Luh Gede Risma Yanti; I Putu Gde Surya Adhitya; Ari Wibawa; I Made Niko Winaya (Universitas Pahlawan Tuanku Tambusai, 2026)
Knee function is the ability of the knee joint to perform movements or activities without pain or limitations such as walking, running, jumping or going up and down stairs. Athletes demand optimal knee conditions with complex movements requiring quadriceps muscle strength and good patellar position, if there is weakness of the quadriceps muscle it can cause an unbalanced pull between the medial and lateral knee. This causes the patella position to experience pulling or tracking which can increase the patellofemoral joint and impact knee function due to pain. This study aims to determine the relationship between quadriceps muscle strength and patellar position to knee function in athletes. This study used a cross-sectional design with 75 athletes aged 15-22 years selected by purposive sampling technique. Quadriceps muscle strength was measured with a hand-held dynamometer, patellar position by visual inspection of the patellar tendon using ultrasonography and knee function with the Knee Injury and Osteoarthritis Outcome Score (KOOS). Statistical analysis used the Spearman's rho bivariate test. A significant correlation was found between left quadriceps muscle strength and the KOOS QOL domain (p=0.031, r=0.250), and a significant correlation was found between right patellar position and the KOOS ADL domain (p=0.042, r=-0.236), but no correlation was found for the other KOOS domains. There was a significant correlation between left quadriceps muscle strength and KOOS QOL, and there was a significant correlation between right patellar position and KOOS ADL in athletes. These findings support the role of quadriceps muscle strength and optimal patellar position in improving knee function.